The Roots of Nationalism: National Identity Formation in Early Modern Europe, 1600-1815 - Jensen, Lotte (Heritage and Memory Studies, 2016)
This collection brings together scholars from a wide range of disciplines to offer perspectives on national identity formation in various European contexts between 1600 and 1815. Contributors challenge the dichotomy between modernists and traditionalists in nationalism studies through an emphasis on continuity rather than ruptures in the shaping of European nations in the period, while also offering an overview of current debates in the field and case studies on a number of topics, including literature, historiography, and cartography.